Wonders of the World - Harris, Nic (NewYork Cambridge University, 2014)
The ancient world had seven 'wonders' - amazing things made by people. Today, people don't agree about what the biggest wonders are. What do you think is a wonder?
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: Elementary level; English language